Biofabrication of Silver Nanoparticles Using the Aqueous Extract of Weaver Ant’s Nest and their In Vitro Cytotoxicity: Biofabrication of Silver Nanoparticles Using the Aqueous Extract of Weaver Ant’s Nest and their In Vitro Cytotoxicity - Sharma, Chacko Vijai (International Journal of Pharmaceutical & Biological Archive, 2020)
Environment has created creative and well-designed ways for developing nanomaterials having intriguing properties. Nanotechnology is having hope to open new avenues to combat and avert diseases using atomic-level fabrication of materials. Herein, we demonstrate the fabrication of silver nanoparticles using aqueous extract of weaver ant’s (Oecophylla smaragdina) nest and its characterization using valuable techniques such as ultraviolet-visible spectroscopy, X-ray diffraction analysis, scanning electron microscopy analysis, Fourier-transform infrared spectroscopy, and atomic force microscopy analysis. Cytotoxicity of newly synthesized silver nanoparticles was analyzed using the Vero cells. By analyzing the results critically, it is hypothesized that synthesis and stabilization of silver nanoparticles were achieved using the molecules present in the aqueous extract of O. smaragdina nest.